2017
DOI: 10.1038/s41523-017-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology, radiology and biological characteristics of interval breast cancers in population mammography screening

Abstract: An interval breast cancer is a cancer that emerges following a negative mammographic screen. This overview describes the epidemiology, and the radiological and biological characteristics of interval breast cancers in population mammography screening. Notwithstanding possible differences in ascertainment of interval breast cancers, there was broad variability in reported interval breast cancer rates (range 7.0 to 49.3 per 10,000 screens) reflecting heterogeneity in underlying breast cancer rates, screening roun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
146
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(164 citation statements)
references
References 49 publications
10
146
2
6
Order By: Relevance
“…These cancers tend to be higher stage and grade at the time of diagnosis whereas screen-detected cancers have been reported to have more indolent molecular characteristics(710). The proportion of interval cancers in screened populations varies from 14% to 38%(1114), depending on screening interval and underlying population breast cancer incidence rates(15). …”
Section: Introductionmentioning
confidence: 99%
“…These cancers tend to be higher stage and grade at the time of diagnosis whereas screen-detected cancers have been reported to have more indolent molecular characteristics(710). The proportion of interval cancers in screened populations varies from 14% to 38%(1114), depending on screening interval and underlying population breast cancer incidence rates(15). …”
Section: Introductionmentioning
confidence: 99%
“…Compared to screen detected cancers, interval cancers have a worse tumor prognosis, biomarker profile, and survival outcome. Following a normal mammogram, 19 This interval cancer rate supports an annual mammography screening recommendation by multiple medical societies. 16,20 In contrast, Kuhl et al demonstrated after a negative MRI screening study, on average, the first screening diagnosis of breast cancer was not made until almost 3 years later, longer than that observed with mammography screening.…”
Section: Discussionmentioning
confidence: 56%
“…Compared to screen detected cancers, interval cancers have a worse tumor prognosis, biomarker profile, and survival outcome. Following a normal mammogram, interval breast cancer rates have been reported to be 8.4–21.1 per 10,000 screens, with the majority of studies based on biennial screening with a larger proportion of interval cancers in the second year . This interval cancer rate supports an annual mammography screening recommendation by multiple medical societies …”
Section: Discussionmentioning
confidence: 68%
“…1,11 Estimation of the incidence of interval cancers in screening programs requires a standardized method for identification, collection, and assessment of the cases. A considerable number of reviews of the incidence of interval cancers in randomized controlled trials and population-based screening programs have been performed, 12-16 as well as reviews on pooled data at regional, national, and international levels.…”
Section: Discussionmentioning
confidence: 99%